Report on marker-assisted selection to identify reproductive behavior in Bh22 population - Hernández, Luis Miguel; Quintero, Constanza; Jauregui, Rosa (Bioversity International and the International Center for Tropical Agriculture, 2022)
Continuing with the fourth cycle of humidicola breeding scheme (Urochloa humidicola (Rendle) Morrone & Zuloaga), a half-sibs population was formed through a genetic cross between suexual population BhSx19 and the apomictic tester CIAT/16888. Using standardized protocols, the identification of the reproduction mode was carried out in the population of hybrids obtained (called Bh22) using the molecular marker p779 / p780. A total of 1,914 (38%) hybrids, from 5,024, showed the apomictic marker, 2,900 (58%) unshowed the apomictic marker and, 210 (4%) were uncertain or did not amplify. The variation in the apomictic and sexual relationship between formed families is presented.